Microwave‐Assisted [3+2] Cycloaddition1 and Suzuki–Miyaura Cross‐Coupling for a Concise Access to Polyaromatic Scaffolds. Issue 33 (9th October 2013) - Hédou, Damien; Deau, Emmanuel; Dubouilh‐Benard, Carole; Sanselme, Morgane; Martinet, Anthony; Chosson, Elizabeth; Levacher, Vincent; Besson, Thierry
Abstract: Novel 3‐(prop‐2‐ynyl)pyrido[2, 3‐ d ]pyrimidin‐4(3 H )‐ones and 3‐(prop‐2‐ynyl)quinazolin‐4(3 H )‐ones have been synthesized in a high‐yielding microwave‐assisted one‐pot procedure. The one‐pot sequence was conveniently extended to the synthesis of commercially unavailable 6‐bromo‐ N 3 ‐propargylpyrido[2, 3‐ d ]pyrimidinone by a regiocontrolled bromination with NBS. The synthetic scaffolds were successfully converted into triazoles by copper(I)‐catalyzed [3+2] cycloaddition and substituted at the 6‐position by Suzuki–Miyaura cross‐coupling in high overall yields. Abstract : A microwave‐assisted one‐pot sequential synthesis involving esterification, formylation, bromination, and cyclization of anthranilic and 2‐aminonicotinic acid derivatives provides access to N 3 ‐propargylquinazolinones or ‐pyridopyrimidinones in high overall yields. Functionalization by [3+2] cycloaddition and Suzuki–Miyaura cross‐coupling rapidly led to 48 novel polyaromatic heterocycles.